从文化翻译理论看影视字幕的翻译 ——以《庆余年》为例 = Cultural translation theory in subtitling practice: a case study of Joy of Life - 关晓昀 Guan, Xiaoyun (Nanyang Technological University, 2025)
本文以苏珊·巴斯奈特（Susan Bassnett）的文化翻译理论为框架，对中国古装剧《庆余年》的英文字幕翻译展开系统性研究。研究采用案例分析法，从词汇、句法和语篇三个维度解构了字幕翻译的跨文化转换机制。 研究发现，《庆余年》字幕翻译以归化策略为主导，通过意译、释义、增译等方法贴近目标语观众的认知习惯，同时辅以异化策略保留部分文化特异性，呈现出归化与异化的动态平衡。在词汇层面，译者对文化负载词进行功能化处理，但存在文化内涵弱化和历史语境消解等问题；句法层面，中文意合结构被重构为英语形合句式，牺牲形式美感但增强逻辑连贯性；语篇层面，通过衔接词显化与意象移植实现叙事功能对等，但诗词韵律与双关修辞流失显著。从巴斯奈特文化翻译理论视角看，《庆余年》字幕翻译既体现了“文化作为翻译单位”的理念，又反映了字幕媒介特殊性对文化传递的限制。本研究不仅揭示了《庆余年》字幕翻译的特点，还探讨了文化翻译理论对影视字幕翻译的启示，为中国古装剧及其他文化类影视作品的字幕翻译提供了理论支持和实践参考。This paper adopts Susan Bassnett’s Cultural Translation Theory as a framework to conduct a systematic analysis of the English subtitles of the Chinese historical drama Joy of Life. Using a case study approach, the research deconstructs the cross-cultural transformation mechanisms of subtitle translation from three dimensions: lexical, syntax, and discourse. The findings reveal that the subtitle translation of Joy of Life is primarily guided by domestication strategies, utilizing methods such as free translation, paraphrasing, and amplification to align with the cognitive habits of the target audience. Meanwhile, foreignization strategies is selectively applied to retain certain cultural specificities, achieving a dynamic equilibrium between domestication and foreignization. At the lexical level, cultural-loaded words are functionally adapted, yet issues such as the dilution of cultural connotations and the loss of historical context remain. At the syntactic level, Chinese paratactic structures are reconstructed into English hypotactic patterns, sacrificing formal elegance for enhanced logical clarity. At the discourse level, narrative functional equivalence is achieved through the explicit use of cohesive devices and the transplantation of imagery, but there is significant loss of poetic rhythm and wordplay rhetoric. From the perspective of Bassnett’s Cultural Translation Theory, the subtitle translation of Joy of Life not only embodies the concept of culture as a unit of translation, but also reflects the constraints imposed by the audiovisual medium on cultural fidelity.This study not only delineates the distinctive features of Joy of Life subtitle translation but also discusses the implications of Cultural Translation Theory for audiovisual subtitle translation, providing theoretical support and practical reference for subtitle translation of Chinese historical dramas and other cultural rich audiovisual productions.